2020
DOI: 10.1177/1753466620914220
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of non-invasive ventilation failure in hematopoietic stem-cell transplantation patients with acute respiratory distress syndrome

Abstract: Background: Non-invasive ventilation (NIV) was one of the first-line ventilation supports for hematopoietic stem-cell transplantation (HSCT) patients with acute respiratory distress syndrome (ARDS). Successful NIV may avoid need for intubation. However, the influence NIV failure had on patients’ outcome and its risk factors were hardly known. Methods: In this retrospective observational study, we reported risk factors and incidence of NIV failure in HSCT patients who were admitted to the Intensive Care Unit (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Compared with those who avoided intubation, those who failed NIV had significantly higher APACHE II scores and serum creatinine and higher proportion of bacterial pneumonia diagnosis. A study of similar size assessing the risk factors for NIV failure in haematopoietic stem cell transplantation patients with ARDS showed elevated creatinine as a risk factor for NIV failure 18. Our study is also consistent with other previous studies showing community-acquired pneumonia, illness severity and extrapulmonary organ dysfunction to be associated with NIV failure 19…”
Section: Discussionsupporting
confidence: 91%
“…Compared with those who avoided intubation, those who failed NIV had significantly higher APACHE II scores and serum creatinine and higher proportion of bacterial pneumonia diagnosis. A study of similar size assessing the risk factors for NIV failure in haematopoietic stem cell transplantation patients with ARDS showed elevated creatinine as a risk factor for NIV failure 18. Our study is also consistent with other previous studies showing community-acquired pneumonia, illness severity and extrapulmonary organ dysfunction to be associated with NIV failure 19…”
Section: Discussionsupporting
confidence: 91%
“…The reported 30-day mortality for HSCT patients with respiratory failure was 50–75%. 10 , 30 To present the estimated mortality rate in the study cohort (62.5% as a mean value), we set the allowable error rate as 6.25% (62.5% × 0.1), confidence interval as 0.9, a sample size of 65 is estimated. All statistical analyses were performed on R (v4.0.4).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in HSCT patients with influenza pneumonia, the reported mortality ranged from 6.3% to 25%, 5 , 6 mortality of Respiratory Syncytial virus pneumonia was 29% to 88%. 7–9 For those who need respiratory supports, their response to mechanical ventilation 10 and extracorporeal membrane oxygenation 11 also differs between patients with different characteristics. Recently, Calfee et al and Bos et al have identified phenotypes of acute respiratory distress syndrome (ARDS) based on clinical and biological data (including serum cytokine levels), patients of different phenotypes have distinct presentations of cytokine levels, other inflammation presentations, clinical outcomes and response to specific treatments.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recent studies have shown that HSCT patients with secondary ARDS have a poor prognosis and an intensive care unit mortality rate of 76%. [4][5][6] RNA-binding protein (RBP) is a general term for a group of proteins that can bind to RNA to assist the regulatory and metabolic processes of RNA. RBPs use RNA-binding domains to recognize target RNAs and participate in various posttranscriptional regulatory processes such as RNA splicing, translocation, polyadenylation, intracellular localization, translation and degradation.…”
Section: Introductionmentioning
confidence: 99%